Professional Development and Learning for Chilean Teachers and Researchers Through Podcasts: The Case of Ricelt - Romero-Villarroel, G (Routledge, 2025)
Purpose: This study explored teacher-researchers professional growth as well as their social and educational contributions after co-designing a professional development and learning program led by the Red de Investigación Chilena en ELT (RICELT), a Chilean Language Teacher Association. Methodology: Employing a qualitative, holistic, and descriptive case study, five ELT teacher researchers from Chile participated in individual semi-structured interviews and a focus group. Findings: The findings reveal three main themes: (a) RICELT PDL Program as a motivation to share equal voices, (b) PDL as a critical pedagogical tool for academic and social change, and (c) RICELT as a supportive LTA for schoolteachers professional and personal development. Originality: The study underscores the transformative potential of Language Teacher Associations in fostering contextually relevant and socially responsible professional growth, advocating for teacher-driven initiatives that empower educators and enhance pedagogical practices, particularly in educational contexts characterized by disparities. © 2025 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Chile; language teacher association; podcast; professional development; teacher-researchers